Alternative approach to the management of postoperative pain after pediatric surgical procedures - Paschoal, Marco [UNESP]; Souza, Juliana [UNESP]; Santos-Pinto, Lourdes [UNESP]; Pansani, Cyneu Aguiar [UNESP] (Jaypee Brothers Medical Publishing, 2014)
This paper reports two clinical cases in which the application of low-level laser therapy (LLLT) enhanced the postoperative symptoms after pediatric surgical procedures. Background: The uses of novel technologies allow more comfort to the patients and ensure a rapid procedure, and LLLT application has shown a positive effect in the prevention of discomfort after invasive procedures. Case description: Low-level laser therapy protocol was applied after surgical removal of supernumerary tooth and frenectomy resulting in less swallow and pain with no need of medication intake. Conclusion: The laser application was well accepted by both children and parents and showed a clinical efficiency in the follow-up examinations beyond the satisfactory quality of wound healing. Clinical significance: The LLLT approach is an excellent adjuvant therapy resource for delivery an optimal postoperative after surgical procedures in children.
Keywords: Low-level laser therapy; Pediatric dentistry; Post-operative pain